A Bibliometric Analysis of Health-Based Gamification - Jawaril Haq Al-Azkiya; Dhea Maulida Rahmah (Ikatan Ahli Informatika Indonesia Nusantara, 2024)
Gamification, the application of game design elements in non-game contexts, has emerged as a promising strategy to promote positive behavior change. Although gamification has shown potential in various domains, including healthcare, a comprehensive analysis of the existing literature is needed to map research trends, influential works, and future directions in the field of health-based gamification. This study used a bibliometric analysis approach, using PoP software for data extraction, VOSviewer for visualization, and Mendeley for reference management. Relevant publications on health-based gamification were identified through a comprehensive search across multiple databases. The extracted data was analyzed to examine temporal trends, thematic clusters, influential authors, and citation patterns. The analysis revealed a steady growth in articles related to health-based gamification, with contributions from researchers in different disciplines. The key thematic groups included gamification applications in mHealth, physical activity interventions, serious games, and adherence. Influential authors and highly cited studies were identified, highlighting foundational work and seminal contributions. This bibliometric study offers a comprehensive overview of the health-based gamification literature, underscoring its interdisciplinary nature and diverse research topics. The findings highlight the potential of gamification in promoting positive health behaviors and facilitating patient engagement. Identified research gaps and emerging trends provide valuable information for future studies, fostering innovation and collaboration in integrating gamification principles into healthcare interventions.